Ревизия семейства Ophryocotylidae (Cestoda, Davaineoidea) - Спасский, А.А.; Корнюшин, В.В. (Вестник зоологии, 1977)
In the authors' opinion only the type genus Ophryocotyle Friis may be preserved in the composition of the considered taxon. In this species the taxon is distinctly isolated from the affinitive subfamily Davaineinae and the family Davaineidae on the whole. The Ophryocotyl zeylanica L i n s t o w, 1906 is distinguished as an independent genus Burtiella gen. n.